Investment Shocks, Tax Evasion and the Consumption Puzzle: A DSGE Analysis with Financial Frictions - Bruno Chiarini; Maria Ferrara; Elisabetta Marzano (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper contributes to the GDP-consumption comovement puzzle literature investigating the role of tax evasion in explaining the consumption path after a Marginal Efficiency of Investment shock. We use an otherwise standard medium-scale New Keynesian DSGE model combining tax evasion with financial frictions à la Bernanke, Gertler, Gilchrist (1999). The main result of our paper shows that tax evasion can considerably shrink the GDP-consumption comovement puzzle area.
Keywords: E22; E32; E44; E51; E62; G10; G21; G30; H20; 330; tax evasion; investment shocks; DSGE modelling; financial frictions; GDP-consumption comovement puzzle